Nomophobia, Smartphone Addiction, Depression, and Anxiety as Predictors of Internet Addiction among Nigerian Preservice Mathematics Teachers - Adeneye Olarewaju A. Awofala; Awele Regina Esealuka (Journal of Informatics and Vocational Education, 2022)
Smartphones and the internet can be very beneficial to their users but if not used properly, also pose great risks to their users. These devices, if used properly, even help in making teaching and learning of perceived ‘tough’ subjects such as mathematics easier. However, smartphone addiction, nomophobia, and internet addiction are now prevalent among modern-day individuals, most especially the younger generation. This poses a problem for the effective teaching and learning of mathematics in Nigeria. This study investigated nomophobia, smartphone addiction, depression, and anxiety as predictors of internet addiction among Nigerian preservice mathematics teachers. The participants consisted of 300 pre-service mathematics teachers randomly selected from the Department of Science and Technology Education, University of Lagos, Nigeria. Seven research questions were answered in the study using the statistical tools of frequency, percentage, mean, standard deviation, Pearson product-moment correlation coefficient, and multiple regression analysis. The results showed a high prevalence of nomophobia and moderate prevalence of smartphone addiction and internet addiction among preservice mathematics teachers. There was a positive relationship between nomophobia, smartphone addiction, anxiety, depression, and internet addiction, of which all were significant predictors of internet addiction. Based on these findings, it was concluded that universities and parents in Nigeria should reduce the prevalence of nomophobia, smartphone addiction, depression, anxiety, and internet addiction in pre-service mathematics teachers in the country.